The relationship between teacher competence, sports facilities, participation, and parental support on learning motivation in Physical Education - Dandi Erianta; Ahmad Lani; Harun Ahmad; Yani Sulis Tyoningsih (Sriwijaya Journal of Sport, 2025)
Research Problems: Student motivation in physical education classes is often low, which affects participation and learning outcomes. Several factors are thought to have an influence, including teacher competence, the quality of sports facilities, student participation, and the role of parents. Research Objectives: Identifying the relationships between variables. These relationships include teacher competence, quality of facilities and infrastructure, participation, and the role of parents in student motivation. These relationships can be viewed both individually and simultaneously. Methods: Quantitative research with correlational tests was applied in this study. The research subjects were all 82 students at SMPN 2 Dau Malang, using a saturated sampling technique. Questionnaires were used to collect data, and descriptive statistical tests and linear regression tests were applied in the research data analysis method. Results: Data analysis in simple linear regression tests and multiple linear tests showed values above 0.05, indicating a significant relationship between all research variables. Conclusion: Research indicates that the factors studied are substantially related to one another, both individually and simultaneously/collectively.